2016
DOI: 10.1089/met.2015.0133
|View full text |Cite
|
Sign up to set email alerts
|

The Best Obesity Indices to Discriminate Type 2 Diabetes Mellitus

Abstract: While WHR had an appropriate discriminatory capability for T2DM in the population of northern Iran, BAI and BMI did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Waist-to-hip ratio, as a measure of obesity or health, has been shown to be a better predictor of cardiovascular disease [37], diabetes [38], and hypercholesterolemia [39] compared with body mass index and waist circumstance. Our finding is similar to studies that showed obesity to be a risk factor of overactive bladder and weight loss to be related to improvements in incontinence status [20, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Waist-to-hip ratio, as a measure of obesity or health, has been shown to be a better predictor of cardiovascular disease [37], diabetes [38], and hypercholesterolemia [39] compared with body mass index and waist circumstance. Our finding is similar to studies that showed obesity to be a risk factor of overactive bladder and weight loss to be related to improvements in incontinence status [20, 40].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that this index gives particularly a notion about being overweight or obese among adults. However, there are many studies performed on adults that do not recommend BMI, instead propose other obesity indices for various purposes such as prediction of hypertension, cardiovascular disease risk classification or as discriminators of in the diagnosis of metabolic syndrome (Chua, Zalilah, Haemamalar, Norhasmah, & Geeta, 2017;Patel et al, 2017;Motamed et al, 2016;Motamed et al, 2017;Fan et al, 2016). Besides, a very recent study has reported that LDL-cholesterol, which is found to be elevated in obese individuals and also known as a risk factor for CVDs is not associated with BMI or waist circumference (Oda, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity indices have recently been a point of interest during the investigation of obesity, risk factors of obesity and obesity-related diseases such as metabolic syndrome, coronary artery disease, acute myocardial infarction and type 2 diabetes (Motamed et al, 2016;Motamed et al, 2017;Mondal & Mishra, 2017;Chua, Zalilah, Haemamalar, Norhasmah, & Geeta, 2017;Patel et al, 2017;Abulmeaty et al, 2017;Tsioufis et al, 2016;Jelavic, Babic & Pintaric, 2017;Liu, Ma, Lou & Zhu, 2016;Tao et al, 2016;Oguoma et al, 2016). So far a great number of studies have been performed on adults with different obesity grades, however research performed on pediatric population ) is scarce.…”
Section: Scope Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…19-24 , Our study subjects were 18 years and older among whom 2859 (56.6%) were male and 2193 (43.4%) were female. Enrolment process is shown in figure 1.…”
Section: Methodsmentioning
confidence: 98%